URO protective effect of Luteolin Nano Suspension on Cyclophosphamide-Induced Hemorrhagic Cystitis in rats - Harikumar, Ravindran Pillai (2016)
Plant-derived extracts have been a great source of materials utilized in medical treatment since immemorial time. According to the World Health Organization (WHO), 70-95 % of human population depends on traditional medicines for their healthcare in which herbal drugs are commonly employed. Luteolin is a bioflavonoid that known for its anti-inflammatory, anti-diabetic, anti-cancer and chemoprotective properties nevertheless it relatively possesses low water solubility and oral bioavailability. The present study was aimed to develop luteolin nanosuspension (LNS) with increased oral bioavailability and to evaluate its protective effect on cyclophosphamide (CP) induced hemorrhagic cystitis (HC) in SD rats. High-pressure homogenization (HPH) technique was used to prepare LNS. LNS showed an enhanced aqueous solubility, which may be attributed to the reduction of particle size from 1649.3 ± 432.23 nm to 420.4 ± 11.26 nm. The oral bioavailability of LNS was determined using HPLC-UV technique, where LNS (30 mg/kg/body weight) and non-modified pure luteolin (30 mg/kg/body weight) were given to rats. LNS significantly improved the oral bioavailability (54.41±14.49%) which was 1.5 fold higher (p<0.05) than pure luteolin (21.72±3.89%). The uroprotective function of LNS was assessed in CP-induced acute hemorrhagic cystitis rats. Male SD rats were divided into four groups. Group- 1 (vehicle control) received normal saline (10 ml/kg/b.w/p.o); group-2 (negative control) received three doses of CP (100 mg/kg/b.w/p.o) on day 6, 8, 10; group-3 (positive control) received MESNA (20 mg/kg/b.w/p.o) and group-4 (test) received LNS (30 mg/kg/b.w/p.o). The relative concentration of glucose, bilirubin, ketone, specific gravity, blood, pH, protein, urobilinogen, nitrite and leukocyte in urine were detected using urine strip test to indicate the incidence the severity of HC. Urinary bladder of CP treated animals reflected severe hemorrhage, inflammation, edema and deep red colouration whereas; LNS significantly improved the morphological deterioration perpetrated by CP. CP treatment has significantly reduced the expression levels of SOD, CAT, GPx, GADD45A and increased the expression levels of TNF-α, p53, NFkB and VEGF. However, LNS administration along with CP have protected the urinary bladder from HC conditions by increasing the expression levels of antioxidant enzymes SOD, CAT and GPx and also by inhibiting the expressions of genes that responsible for bladder inflammation including TNF-α , NFkB and VEGF. Moreover, LNS treatment significantly elevated the serum levels of cytokines IL-2 and IL-4, which may reduce the CP-induced bladder hemorrhage, inflammation and associated symptoms. Besides, the hepatic enzyme level of AST, ALT, ALP, LDH, total protein and creatinine were normalized in LNS treatment group. The histological examination demonstrated that uroepithelial tissue damages were also prevented by the LNS in CP-induced hemorrhagic cystitis pathogenesis. In conclusion, HPH technique could serve as an ideal, easy, safe and reproducible technique to formulate LNS. LNS protected the urinary bladder from CP-induced toxicity by modulating the release of various inflammatory mediators; enhancing the immune status of the host; restoring the oxidative/redox mechanisms and effectively clearing the toxic metabolite residues in the urinary bladder. LNS with its anti-oxidative, anti-inflammatory and chemoprotective activities had alleviated the HC conditions induced by CP. The current study supports the use of luteolin in nanosuspension form (LNS) as uroprotectant along with drugs that pathologically affect urinary bladder.